PENERAPAN VIDEO PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR PEMBELAJARAN DARING PADA SISWA SMP - Windi Melani Nursidiq; Aflich Yusnita Fitrianna; Luvy Sylviana Zanthy (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study was conducted with the goal of enhancing seventh-grade junior high school students' online learning results by implementing learning videos, during the covid-19 pandemic learning was carried out through WhatsApp groups (WAG). This type of research is Classroom Action Research (CAR). The subjects in this study were 13th grade junior high school students in one of the junior high schools in West Bandung Regency. The research method used is descriptive qualitative. The research instrument used is in the form of test questions. The steps of classroom action research are (1) planning, (2) implementation, (3) observation and (4) reflection, which were carried out in this Classroom Action Research (CAR) in 2 cycles. Based on the results of learning mathematics students who reach the KKM cycle is 69.23%. From the results of this study, it can be concluded that online learning with the application of learning videos can improve learning outcomes for junior high school students.